Millennial Generation Optimizing Organizational Commitment with Internal Communication - Widya Parimita (Faculty of Economics, State University of Jakarta., 2021)
The research focusing on expanding scientific studies to see the effect of internal communication by checking employee’s perception in keeping the company internal symmetric communication for maintaining the commitment to the company. This research further discuss about the organization casual commitment relationship, internal communication, meaning of works and work engagement. The method conducted in this research is through survey with descriptive approach. Causal modeling or relations and cause, or known as path analysis is the model used for this research. SEM (Structural Equation Modeling) with SMARTPLS 3.0 program. The direct effect from exogen variable to the endogen will be analyzed through the Partial Least Square. Research said that there is a positive and significant influence of internal communication to colleague, organization commitment and meaning of works. Furthermore, meaning of works is giving a positive influence and significant to organization commitment and work engagement. The outcome of this research can be used as reference and information for developing knowledge, specifically in the field of human resource management in developing theory in organizational commitment.